2006
DOI: 10.1089/jmf.2006.9.491
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genistein Isoflavone on Matrix Metalloproteinase-2 Expression in Prostate Cancer Cells

Abstract: We investigated the expression of matrix metalloproteinase (MMP)-2 in human LNCaP and PC3 prostate cancer cell lines in response to genistein exposure. Initially we studied the phytosensitivity of the cells to genistein using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay to determine percentage cell viability/inhibition and the terminal deoxynucleotidyl transferase-mediated fluorescein-dUTP nick end-labeling apoptosis assay to assess the type of cell death. The results revealed that ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 36 publications
2
20
0
1
Order By: Relevance
“…30) Several MMP inhibitors have been identified from natural sources such as resveratrol, 31) theaflavins, 32) catechins, 33) curcumin [34][35][36] and genistein. 37) In this study, we showed that anethole inhibited the activity of MMP-2 and -9 and simultaneously increased the activity of TIMP-1 in HT 1080 cells. The data suggest that anethole possesses the antimetastatic activity and is a potent drug for anti-cancer treatment.…”
Section: Discussionmentioning
confidence: 60%
“…30) Several MMP inhibitors have been identified from natural sources such as resveratrol, 31) theaflavins, 32) catechins, 33) curcumin [34][35][36] and genistein. 37) In this study, we showed that anethole inhibited the activity of MMP-2 and -9 and simultaneously increased the activity of TIMP-1 in HT 1080 cells. The data suggest that anethole possesses the antimetastatic activity and is a potent drug for anti-cancer treatment.…”
Section: Discussionmentioning
confidence: 60%
“…Gn-induced decrease in MMP-2 expression levels in cancer cells has been reported previously. 39 MMP-2 expression in cancer cells has been associated with active invasion and metastasis of many human cancer cells. This indicates the potential chemopreventive significance of Gn-Se combination treatment as observed in the present studies, especially if this could be extrapolated into in vivo studies in PC3/LNCaP animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genistein also blocked VEGF/bFGF-induced uPA and PA inhibitor-1 expression. Later, Kumi-Diaka et al [100] also documented inhibition of MMP-2 expression in cells treated with genistein. Additionally, genistein reduced the mRNA level of several MMPs including MMP-2, MMP-3, MMP-13, and MMP-15 [101].…”
Section: Antiangiogenic Effect Of Soy Isoflavonoidsmentioning
confidence: 99%